miRNA-Based Signature Associated With Tumor Mutational Burden in Colon Adenocarcinoma - Xue, Weijie; Wang, Yixiu; Xie, Yuwei; Yang, Chenyu; Gong, Zhiqi; Guan, Chunyang; Wei, Chuqing; Zhu, Chengzhan; Niu, Zhaojian (Frontiers in Oncology, 2021)
A colon adenocarcinoma (COAD) is one of the most common malignant tumors. The tumor mutation burden (TMB) has become an independent biomarker for predicting the response of immune checkpoint inhibitors. MiRNA plays an important role in cancer-related immune regulation. However, in COAD the relationship between the expression of miRNA and the TMB is unclear. Therefore, the transcriptome profiling data, clinical data, mutation annotation data, and miRNA expression profiles for cases of COAD were downloaded from the TCGA database. Subsequently, 323 COAD cases were randomly divided into training, and test sets. The differential expression of miRNAs in the high and low TMB groups in the training set was obtained as a signature using the least absolute shrinkage and selection operator (LASSO) logistic regression, and verified in the test set. Based on the LASSO method, principal component analysis (PCA), and ROC, we found that the signature was credible because it can discriminate between high and low TMB levels. In addition, the correlation between the 18-miRNA-based signature and immune checkpoints was performed and followed by the use of QRT-PCR to measure the relative expression of 18 miRNAs in COAD patients. The miRNA-based model had a strong positive correlation with TMB, and a weak positive correlation with CTLA4 and CD274 (PD-L1). However, there was no correlation between the model and the SNCA (PD-1). Finally, enrichment analysis of the 18 miRNAs was performed to explore their biological function. The results demonstrated that the 18 miRNAs were involved in the process of immunity, and the cancer pathways. In conclusion, the 18-miRNA-based signature can effectively predict and discriminate between the different TMB levels of COADs and provides a guide for its treatment with ICIs.